Health Care Needs an,d Services among Female Inmates of Misamis Oriental Provincial Jail and Rehabilitation Center - Neri, Donna Lou E. (JPAIR Multidisciplinary Research, 2008)
The study aimed to determine the health care needs, services, and health conditions of 21 female inmates at the Misamis Oriental Provincial Jail and Rehabilitation Center. It assessed health care needs and services such as food, water, sleeping conditions, jail facilities, environment, medical services, and love and belongingness. Using a descriptive method with universal sampling, data were tabulated and analyzed statistically. Findings showed that respondents were undecided about the quality of most services but disagreed that sleeping conditions were satisfactory. They reported receiving adequate love and belongingness. Health problems identified included kidney infections, back pain, impaired vision, cough, ulcers, difficulty breathing, pregnancy-related issues, chest pain, visual changes, smoking habits, weight/appetite changes, alcohol use, itching, and pain. Despite a low rate of illnesses, the study found no significant relationship between health needs and services. Overall, the health care needs and services were below UN standards, highlighting the need for improvements to ensure detainees’ well-being. The lack of significant health issues among respondents suggests that while health care services are subpar, they are not leading to widespread health crises. However, addressing these deficiencies is crucial for aligning with international standards and ensuring humane treatment of inmates.